A high strength bolt
By introducing Th and Hf elements into high-strength bolts and depositing a NiZr-Pr wear-resistant layer on the surface, the problem of insufficient strength and wear resistance of bolts at high temperatures is solved and higher high-temperature strength and wear resistance are achieved.
Patent Information
- Application Number
- CN202410794704.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-06-19
AI Technical Summary
High-strength bolts have low strength and poor wear resistance at high temperatures, making them difficult to meet the application needs in various high-temperature scenarios.
By introducing a specific combination of elements into the bolt components, such as 0.08%~0.15% Th and 0.1%~0.3% Hf, and depositing a NiZr-Pr wear-resistant layer on the bolt surface, the strength and resistance of the bolts at high temperatures are improved. Abrasive.
Significantly improves the strength and wear resistance of bolts at high temperatures, can more effectively withstand high temperatures and alternating loads in high temperature environments, and reduce wear.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fasteners, and in particular to a high-strength bolt. Background Art
[0002] High-strength bolts are widely used in various engineering practices due to their advantages such as reliable force and good stability. However, due to the complex actual application environment, bolts need to withstand high temperatures and alternating loads in high-temperature environments, resulting in low high-temperature strength of high-strength bolts. In addition, bolts are required to have excellent wear resistance at high temperatures to reduce wear during repeated disassembly. Therefore, it is necessary to develop a bolt with high strength and excellent wear resistance at high temperatures to meet the application needs in various high-temperature scenarios. Summary of the invention
[0003] The present invention provides a high-strength bolt, which solves the problem of low strength and poor wear resistance of the high-strength bolt at high temperature in the related art.
[0004] The technical solution of the present invention is as follows:
[0005] The present invention provides a high-strength bolt, comprising a bolt, wherein the bolt is composed of the following components in mass percentage: C 0.1%-0.15%, Si 0.3%-0.45%, Mn 0.35%-0.65%, Cr 1%-2.5%, Ni 0.6%-1%, Mo 0.3%-0.6%, Ti 0.35%-0.5%, Al 0.15%-0.25%, Nb 0.05%-0.08%, V 0.15%-0.20%, Th 0.08%-0.15%, Hf0.1%-0.3%, and the balance is Fe and other inevitable impurities.
[0006] As a further technical solution, the bolt is composed of the following components in mass percentage: C 0.1%~0.15%, Si 0.3%~0.45%, Mn 0.35%~0.65%, Cr 1%~2.5%, Ni 0.6%~1%, Mo 0.3%~0.6%, Ti 0.35%~0.5%, Al 0.15%~0.25%, Nb 0.05%~0.08%, V 0.15%~0.20%, Th 0.08%~0.15%, Hf 0.1%~0.3%, and the balance is Fe and other inevitable impurities, and 0.4%≤V+Th+Hf≤0.55%.
[0007] In the present invention, the strength and wear resistance of the bolt at high temperature are further improved by limiting the sum of the V, Th and Hf components to 0.4% to 0.55%.
[0008] As a further technical solution, the bolt is composed of the following components in mass percentage: C 0.1%~0.15%, Si 0.3%~0.45%, Mn 0.35%~0.65%, Cr 1%~2.5%, Ni 0.6%~1%, Mo 0.3%~0.6%, Ti 0.35%~0.5%, Al 0.15%~0.25%, Nb 0.05%~0.08%, V 0.15%~0.20%, Th 0.08%~0.15%, Hf 0.1%~0.3%, Sm 0.1%~0.14%, and the balance is Fe and other inevitable impurities, and 0.4%≤V+Th+Hf≤0.55%.
[0009] In the present invention, 0.1% to 0.14% of Sm is introduced on the basis of limiting the sum of the V, Th and Hf components to 0.4% to 0.55%, thereby further improving the strength and wear resistance of the bolt at high temperatures.
[0010] As a further technical solution, it also includes a NiZr-Pr wear-resistant layer deposited on the surface of the bolt; the NiZr-Pr wear-resistant layer includes a NiZr layer and a Pr layer in sequence from bottom to top.
[0011] In the present invention, a NiZr-Pr wear-resistant layer is arranged on the surface of the bolt, and the NiZr layer makes the bolt matrix and the Pr layer more tightly combined, thereby further improving the wear resistance of the bolt at high temperature.
[0012] As a further technical solution, the thickness of the NiZr layer is 0.3-0.5 μm; the thickness of the Pr layer is 0.4-0.8 μm.
[0013] As a further technical solution, the mass percentage of Zr in the NiZr layer is 15% to 20%.
[0014] The present invention also proposes a preparation process of the high-strength bolt, comprising the following steps:
[0015] S1. Weighing raw materials according to the components in the mass percentage, melting, refining, and casting to obtain bolt blanks;
[0016] S2, heat treating the bolt blank and processing it into a shape to obtain a bolt;
[0017] S3. After depositing a NiZr layer on the surface of the bolt using a NiZr target, further depositing a Pr layer on the NiZr layer using a Pr target to obtain a bolt containing a NiZr-Pr wear-resistant layer.
[0018] As a further technical solution, the processing and forming includes polishing, thread rolling and cleaning treatment in sequence.
[0019] As a further technical solution, in step S2, the heat treatment is first heated to 1050~1090°C at a heating rate of 100~120°C / h, kept at that temperature for 2~4h, and then cooled to room temperature with the furnace at a cooling rate of 130~160°C / h.
[0020] As a further technical solution, in step S3, the target current during the deposition is 50-80A, and the vacuum degree is 0.4Pa-0.8Pa.
[0021] The working principle and beneficial effects of the present invention are:
[0022] In the present invention, by introducing 0.08% to 0.15% Th and 0.1% to 0.3% Hf into the bolt component, the strength and wear resistance of the bolt at high temperature are significantly improved. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] High-strength bolts, including bolts, the bolts are composed of the following components in mass percentage: C 0.1%, Si 0.3%, Mn 0.35%, Cr 1%, Ni 0.6%, Mo 0.3%, Ti 0.35%, Al 0.15%, Nb 0.05%, V 0.15%, Th 0.08%, Hf 0.1%, the balance being Fe and other inevitable impurities;
[0026] The preparation process of high-strength bolts includes the following steps:
[0027] S1. Weighing raw materials according to the components of the bolts, melting, refining, and casting to obtain bolt blanks;
[0028] S2. Heat-treat the bolt blank by first heating it to 1090°C at a heating rate of 100°C / h, keeping it at that temperature for 2h, and then cooling it to room temperature with the furnace at a cooling rate of 160°C / h. After polishing, thread rolling and cleaning, the bolt is obtained.
[0029] Example 2
[0030] High-strength bolts, including bolts, the bolts are composed of the following components in mass percentage: C 0.15%, Si 0.45%, Mn 0.65%, Cr 2.5%, Ni 1%, Mo 0.6%, Ti 0.5%, Al 0.25%, Nb 0.08%, V 0.20%, Th 0.15%, Hf0.3%, the balance being Fe and other inevitable impurities;
[0031] The preparation process of high-strength bolts includes the following steps:
[0032] S1. Weighing raw materials according to the components of the bolts, melting, refining, and casting to obtain bolt blanks;
[0033] S2. Heat-treat the bolt blank by first heating it to 1050°C at a heating rate of 120°C / h, keeping it at that temperature for 4 hours, and then cooling it to room temperature with the furnace at a cooling rate of 130°C / h. After polishing, thread rolling and cleaning, the bolt is obtained.
[0034] Example 3
[0035] High-strength bolts, including bolts, the bolts are composed of the following components in mass percentage: C 0.13%, Si 0.4%, Mn 0.45%, Cr 1.98%, Ni 0.85%, Mo 0.5%, Ti 0.4%, Al 0.22%, Nb 0.07%, V 0.16%, Th 0.09%, Hf 0.12%, the balance being Fe and other inevitable impurities;
[0036] The preparation process of high-strength bolts includes the following steps:
[0037] S1. Weighing raw materials according to the components of the bolts, melting, refining, and casting to obtain bolt blanks;
[0038] S2. Heat-treat the bolt blank by first heating it to 1080°C at a heating rate of 110°C / h, keeping it at that temperature for 3h, and then cooling it to room temperature with the furnace at a cooling rate of 150°C / h. After polishing, thread rolling and cleaning, the bolt is obtained.
[0039] Example 4
[0040] The only difference between this embodiment and embodiment 3 is that the bolt is composed of the following components in mass percentage: C 0.13%, Si 0.4%, Mn 0.45%, Cr 1.98%, Ni 0.85%, Mo 0.5%, Ti 0.4%, Al 0.22%, Nb 0.07%, V 0.18%, Th 0.13%, Hf 0.27%, and the balance is Fe and other inevitable impurities.
[0041] Example 5
[0042] The only difference between this embodiment and Embodiment 3 is that the bolt is composed of the following components in mass percentage: C 0.13%, Si 0.4%, Mn 0.45%, Cr 1.98%, Ni 0.85%, Mo 0.5%, Ti 0.4%, Al 0.22%, Nb 0.07%, V 0.17%, Th 0.11%, Hf 0.12%, and the balance is Fe and other inevitable impurities.
[0043] Example 6
[0044] The only difference between this embodiment and embodiment 3 is that the bolt is composed of the following components in mass percentage: C 0.13%, Si 0.4%, Mn 0.45%, Cr 1.98%, Ni 0.85%, Mo 0.5%, Ti 0.4%, Al 0.22%, Nb 0.07%, V 0.2%, Th 0.1%, Hf 0.25%, and the balance is Fe and other inevitable impurities.
[0045] Example 7
[0046] The only difference between this embodiment and Embodiment 6 is that the bolt is composed of the following components in mass percentage: C 0.13%, Si 0.4%, Mn 0.45%, Cr 1.98%, Ni 0.85%, Mo 0.5%, Ti 0.4%, Al 0.22%, Nb 0.07%, V 0.2%, Th 0.1%, Hf 0.25%, Sm 0.1%, and the balance is Fe and other inevitable impurities.
[0047] Example 8
[0048] The only difference between this embodiment and Embodiment 6 is that the bolt is composed of the following components in mass percentage: C 0.13%, Si 0.4%, Mn 0.45%, Cr 1.98%, Ni 0.85%, Mo 0.5%, Ti 0.4%, Al 0.22%, Nb 0.07%, V 0.2%, Th 0.1%, Hf 0.25%, Sm 0.14%, and the balance is Fe and other inevitable impurities.
[0049] Example 9
[0050] The difference between this embodiment and embodiment 8 is only that the high-strength bolt includes a bolt and a NiZr layer deposited on the surface of the bolt;
[0051] The preparation process of high-strength bolts includes the following steps:
[0052] S1. Weighing raw materials according to the components of the bolts, melting, refining, and casting to obtain bolt blanks;
[0053] S2. Heat-treating the bolt blank by first heating it to 1080°C at a heating rate of 110°C / h, keeping it at that temperature for 3h, and then cooling it to room temperature with the furnace at a cooling rate of 150°C / h. After polishing, thread rolling and cleaning, a bolt is obtained.
[0054] S3. Multi-arc ion plating: A NiZr layer is deposited on the surface of the bolt using a NiZr target to obtain a bolt containing a NiZr layer; wherein the target current during deposition is 50 A, the vacuum degree is 0.8 Pa, and the thickness of the NiZr layer is 0.3 μm.
[0055] Example 10
[0056] The difference between this embodiment and embodiment 8 is only that the high-strength bolt includes a bolt and a Pr layer deposited on the surface of the bolt;
[0057] The preparation process of high-strength bolts includes the following steps:
[0058] S1. Weighing raw materials according to the components of the bolts, melting, refining, and casting to obtain bolt blanks;
[0059] S2. Heat-treating the bolt blank by first heating it to 1080°C at a heating rate of 110°C / h, keeping it at that temperature for 3h, and then cooling it to room temperature with the furnace at a cooling rate of 150°C / h. After polishing, thread rolling and cleaning, a bolt is obtained.
[0060] S3. Multi-arc ion plating: A Pr layer is deposited on the surface of the bolt using a Pr target to obtain a bolt containing a Pr layer; wherein the target current during deposition is 50A, the vacuum degree is 0.8Pa, and the thickness of the Pr layer is 0.4μm.
[0061] Embodiment 11
[0062] The difference between this embodiment and embodiment 8 is only that the high-strength bolt includes a bolt and a Pr-NiZr layer deposited on the surface of the bolt;
[0063] The preparation process of high-strength bolts includes the following steps:
[0064] S1. Weighing raw materials according to the components of the bolts, melting, refining, and casting to obtain bolt blanks;
[0065] S2. Heat-treating the bolt blank by first heating it to 1080°C at a heating rate of 110°C / h, keeping it at that temperature for 3h, and then cooling it to room temperature with the furnace at a cooling rate of 150°C / h. After polishing, thread rolling and cleaning, a bolt is obtained.
[0066] S3. Multi-arc ion plating: After a Pr layer is deposited on the surface of the bolt using a Pr target, a NiZr layer is deposited on the Pr layer using a NiZr target to obtain a bolt containing a Pr-NiZr layer; wherein the target current during deposition is 50A, the vacuum degree is 0.8Pa, the thickness of the Pr layer is 0.4μm, and the thickness of the NiZr layer is 0.3μm.
[0067] Example 12
[0068] The difference between this embodiment and embodiment 8 is only that the high-strength bolt includes a bolt and a NiZr-Pr layer deposited on the surface of the bolt;
[0069] The preparation process of high-strength bolts includes the following steps:
[0070] S1. Weighing raw materials according to the components of the bolts, melting, refining, and casting to obtain bolt blanks;
[0071] S2. Heat-treating the bolt blank by first heating it to 1080°C at a heating rate of 110°C / h, keeping it at that temperature for 3h, and then cooling it to room temperature with the furnace at a cooling rate of 150°C / h. After polishing, thread rolling and cleaning, a bolt is obtained.
[0072] S3. Multi-arc ion plating: After depositing a NiZr layer on the surface of the bolt using a NiZr target, a Pr layer is deposited on the NiZr layer using a Pr target to obtain a bolt containing a NiZr-Pr layer; wherein the target current during deposition is 50A, the vacuum degree is 0.8Pa, the thickness of the Pr layer is 0.4μm, and the thickness of the NiZr layer is 0.3μm.
[0073] Embodiment 13
[0074] The only difference between this embodiment and embodiment 12 is that the target current during deposition in step S3 is 80 A, the vacuum degree is 0.4 Pa, the thickness of the Pr layer is 0.8 μm, and the thickness of the NiZr layer is 0.5 μm.
[0075] Comparative Example 1
[0076] The only difference between this comparative example and Example 3 is that the bolt consists of the following components in mass percentage: C 0.13%, Si 0.4%, Mn 0.45%, Cr 1.98%, Ni 0.85%, Mo 0.5%, Ti 0.4%, Al 0.22%, Nb 0.07%, V 0.16%, Th 0.21%, and the balance is Fe and other inevitable impurities.
[0077] Comparative Example 2
[0078] The only difference between this comparative example and Example 3 is that the bolt consists of the following components in mass percentage: C 0.13%, Si 0.4%, Mn 0.45%, Cr 1.98%, Ni 0.85%, Mo 0.5%, Ti 0.4%, Al 0.22%, Nb 0.07%, V 0.16%, Hf 0.21%, and the balance is Fe and other inevitable impurities.
[0079] According to the standard GB / T 228.2-2015 "Metallic Material High Temperature Tensile Test Method", the performance test was carried out: the bolts prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were respectively subjected to high temperature (700°C) upper yield strength test, and the bolts prepared in Examples 1 to 13 and Comparative Examples 1 to 2 were respectively subjected to high temperature (700°C) friction and wear test using a UMT-Tribolab multifunctional friction and wear tester. The test results are shown in Tables 1 and 2.
[0080] Table 1 Upper yield strength and wear volume test results
[0081]
[0082] Table 2 Wear volume test results of wear resistance
[0083]
[0084] By comparing the data of Examples 1 to 8 and Comparative Examples 1 to 2, it is found that compared with Comparative Examples 1 to 2, the bolts prepared in Examples 1 to 8 have higher upper yield strength and smaller wear volume at 700°C, indicating that by introducing 0.08% to 0.15% Th and 0.1% to 0.3% Hf into the bolt components, the strength and wear resistance of the bolts at high temperatures are significantly improved.
[0085] By comparing the data of Examples 3 to 6, it is found that compared with Examples 3 to 4, the bolts prepared in Examples 5 to 6 have higher upper yield strength and smaller wear volume at 700°C, indicating that limiting the sum of the V, Th and Hf components to 0.4% to 0.55% further improves the strength and wear resistance of the bolts at high temperatures.
[0086] By comparing the data of Examples 6 to 8, it is found that compared with Example 6, the bolts prepared in Examples 7 to 8 have higher upper yield strength at 700°C and smaller wear volume, indicating that the introduction of 0.1% to 0.14% Sm on the basis of limiting the sum of V, Th and Hf components to 0.4% to 0.55% further improves the strength and wear resistance of the bolts at high temperatures.
[0087] By comparing the data of Examples 9 to 13, it is found that compared with Examples 9 to 11, the bolts prepared in Examples 12 to 13 have a smaller wear volume at 700°C, indicating that a NiZr-Pr wear-resistant layer is provided on the surface of the bolt, and the NiZr layer makes the bolt base and the Pr layer more tightly combined, thereby further improving the wear resistance of the bolt at high temperature.
[0088] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength bolt, characterized in that: The invention comprises a bolt, wherein the bolt is composed of the following components in percentage by mass: C 0.1%-0.15%, Si 0.3%-0.45%, Mn 0.35%-0.65%, Cr 1%-2.5%, Ni 0.6%-1%, Mo 0.3%-0.6%, Ti 0.35%-0.5%, Al 0.15%-0.25%, Nb 0.05%-0.08%, V 0.15%-0.20%, Th 0.08%-0.15%, Hf 0.1%-0.3%, and the balance is Fe and other inevitable impurities.
2. A high strength bolt according to claim 1, characterized in that: The bolt is composed of the following components in mass percentage: C 0.1%-0.15%, Si 0.3%-0.45%, Mn 0.35%-0.65%, Cr 1%-2.5%, Ni 0.6%-1%, Mo0.3%-0.6%, Ti 0.35%-0.5%, Al 0.15%-0.25%, Nb 0.05%-0.08%, V 0.15%-0.20%, Th 0.08%-0.15%, Hf 0.1%-0.3%, the balance is Fe and other inevitable impurities, and 0.4%≤V+Th+Hf≤0.55%.
3. A high strength bolt according to claim 2, characterized in that: The bolt is composed of the following components in mass percentage: C 0.1%-0.15%, Si 0.3%-0.45%, Mn 0.35%-0.65%, Cr 1%-2.5%, Ni 0.6%-1%, Mo0.3%-0.6%, Ti 0.35%-0.5%, Al 0.15%-0.25%, Nb 0.05%-0.08%, V 0.15%-0.20%, Th 0.08%-0.15%, Hf 0.1%-0.3%, Sm 0.1%-0.14%, and the balance is Fe and other inevitable impurities, and 0.4%≤V+Th+Hf≤0.55%.
4. A high strength bolt according to claim 3, characterized in that: It also includes a NiZr-Pr wear-resistant layer deposited on the surface of the bolt; the NiZr-Pr wear-resistant layer includes a NiZr layer and a Pr layer in order from bottom to top.
5. A high strength bolt according to claim 4, characterized in that: The thickness of the NiZr layer is 0.3-0.5 μm; the thickness of the Pr layer is 0.4-0.8 μm.
6. A high strength bolt according to claim 4, characterized in that: The mass percentage of Zr in the NiZr layer is 15% to 20%.
7. A process for preparing a high-strength bolt according to any one of claims 4 to 6, characterized in that: The following steps are involved: S1. Weighing raw materials according to the components in the mass percentage, melting, refining, and casting to obtain bolt blanks; S2, heat treating the bolt blank and processing it into a shape to obtain a bolt; S3. After depositing a NiZr layer on the surface of the bolt using a NiZr target, further depositing a Pr layer on the NiZr layer using a Pr target to obtain a bolt containing a NiZr-Pr wear-resistant layer.
8. The process for preparing a high-strength bolt according to claim 7, characterized in that: The processing and forming includes polishing, thread rolling and cleaning in sequence.
9. The process for preparing a high-strength bolt according to claim 7, characterized in that: In step S2, during the heat treatment, the temperature is first raised to 1050-1090°C at a heating rate of 100-120°C / h, kept at that temperature for 2-4 hours, and then cooled to room temperature with the furnace at a cooling rate of 130-160°C / h.
10. The process for preparing a high-strength bolt according to claim 7, characterized in that: In step S3, the target current during the deposition is 50-80A, and the vacuum degree is 0.4-0.8Pa.
Citation Information
Patent Citations
High-strength and high-toughness alloy steel
CN105624555A
15.9-grade corrosion-resistant high-strength bolt steel and production method and heat treatment method thereof
CN114058974A